1984
DOI: 10.1002/cyto.990050307
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA cytophotometry in prostate carcinoma

Abstract: Cytologic evaluation of aspired samples of palpable nodules in the human prostate developed into a routine method, since Esposti (5) classified carcinoma with high (Gl), moderate (G2), and poor (G3) differentiation and evaluated the prognostic importance.The malignant cells frequently have a different DNA content than do normal cells (1,3,7,8,13). The purpose of this study was to determine the DNA content of prostate cancer cells before and during endocrine therapy, to compare it with the cytologic grading, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In 1984 Seppelt et al [74] reported good correlation between clinical follow up and progressive changes in the DNA histogram, as obtained by static cytophotometry on FNA material. However, progressive changes of the histogram were seen in more than half the cases with clinical remission.…”
Section: Densitometry and Prostate Adenocarcinomamentioning
confidence: 99%
“…In 1984 Seppelt et al [74] reported good correlation between clinical follow up and progressive changes in the DNA histogram, as obtained by static cytophotometry on FNA material. However, progressive changes of the histogram were seen in more than half the cases with clinical remission.…”
Section: Densitometry and Prostate Adenocarcinomamentioning
confidence: 99%
“…We were interested in determining if the information generated by DNA analysis, reflecting mostly prostatectomy tissue, could also be obtained by flow cytometry before prostatectomy from the very small, multiple, core biopsies of the prostate divided into normal segments versus segments containing malignant glands. Although there are some reports using the DNA measurement methods of image cytometry from fine needle aspirate (FNA) material [9,10], as well as flow cytometry to measure the DNA content of fresh FNA material [11,12] or freshly minced core biopsies [13,14] of the prostate, we are not aware of any reports utilizing flow cytometry to analyze fixed, paraffin-embedded biopsies. One potential benefit of using the fixed, paraffin-embedded core biopsies, instead of fresh tissue when using flow cytometry, is the technical advantage of being able to select and analyze different areas of the core biopsies enriched for malignant versus benign cells.…”
Section: Introductionmentioning
confidence: 99%
“…A more favorable response of tumors to endocrine therapy and a longer progression-free and over all survival rate of patients receiving such therapy have been observed in diploid and tetraploid cases than in triploid or hypertetraploid cases [64,65,71]. Histological grade or clinical stage did not predict the response to endocrine therapy [65,71], New aneuploid peaks often appear in nonresponsive tumors [77] suggesting that the evolvement of tumor karyotype may have contributed to the disease progression. Ekman et al [66] showed that DNA aneuploid prostatic tumors were more often andro gen-receptor-negative than diploid tumors.…”
Section: Introductionmentioning
confidence: 99%